IMPLEMENTING FAMILY HOPE PROGRAM IN INCREASING HEALTH AND EDUCATION FOR THE VERY POOR HOUSEHOLD - Depi Putri; Zulkipli Lessy; Robeet Thadi (Social Welfare Study Program, 2022)
Abstract. The Indonesian Family Hope Program (PKH) is both a Conditional Cash Transfer program (BTB) and a Social Protection Program, and is among the first cluster of modern poverty alleviation strategies implemented in Indonesia. The PKH has been able to meet some of the needs of the poor for access to health care and for education. Such services in Indonesia are difficult to obtain, especially by Very Poor Households (RTSM/KSM) in Umbulharjo District, Yogyakarta City. This study examines implementation of PKH for RTSM/KSM families and assesses effectiveness of PKH toward improving maternal health and children’s education. Qualitative descriptive research collected in-depth information about, and from, seven PKH participants living in the Umbulharjo District of Yogyakarta City. These informants were selected by purposive sampling as representative of health care needs, educational issues, and reliability of information about services. Using their documented observations, the subsequent analysis consisted of data reduction, data presentation, and data inference techniques. Results documented characteristics of the program and experiences of the participants, as follows. (1) These seven PKH recipients were of productive age, but had a poor quality of formal education; were part of an extended family structure, but also had poor housing conditions; and were living amid overall poor economic conditions, while having very low income. (2) All of the participants were in the RTSM/KSM sector. (3) They were among the 42.86%of recipients having family conditions below Regency Minimum Wage (UMK) in 2018, and the 57.14% of recipients having women supporting the family. (4) Implementation of the Family Hope Program effectively improved marital health and medical health for these RTSM/KSM families, with a reduction of burdens and an increase in education. Keywords: Family Hope Program, health, education, poverty. Abstrak. PKH merupakan program Bantuan Tunai Bersyarat (BTB) dan perlindungan sosial yang termasuk dalam klaster pertama strategi penanggulangan kemiskinan di Indonesia. Program ini sudah mampu menjawab kebutuhan dan akses masyarakat miskin terhadap kesehatan dan pendidikan yang masih sulit diperoleh, khususnya oleh RTSM/KSM di Kecamatan Umbulharjo Kota Yogyakarta. Penelitian ini bertujuan (1) mengetahui pelaksanaan PKH bagi keluarga RTSM/KSM di Kecamatan Umbulharjo Kota Yogyakarta (2) mengetahui efektivitas PKH ini dalam meningkatkan kesehatan ibu hamil dan pendidikan anak. Penelitian ini adalah deskriptif kualitatif, yang dirancang untuk mengumpulkan data dan informasi secara mendalam tentang peserta PKH di Kecamatan Umbulharjo, Kota Yogyakarta DIY. Informan dipilih secara purposive dan bukan pada jumlah yang banyak atau acak melainkan lebih pada keterwakilan masalah dan keterandalan informasi dan observasi terhadap tujuh peserta PKH sebagai informan. Teknik Analisis Data menggunakan (1) Reduksi data (2) Penyajian data (3) Penyimpulan data. Hasil penelitian menunjukkan bahwa: (1) karakteristik peserta PKH berusia produktif, kualitas pendidikan formal rendah, menganut sistem keluarga besar, dengan kondisi hunian rumah kurang layak, kondisi ekonomi kurang yang ditandai penghasilan rendah; (2) 100% peserta PKH di Kecamatan Umbulharjo adalah RTSM/KSM. (3) 42,86% kondisi keluarga peserta PKH di Kecamatan Umbulharjo berada di bawah Upah Minimum Kabupaten/Kota (UMK) DIY tahun 2018 sebab dalam keluarga RTSM/KSM yang menjadi tulang punggung keluarga adalah perempuan (57.14%); (4) pelaksanaan program keluarga harapan (PKH) di Kecamatan Umbulharjo merupakan salah satu program yang efektif dalam meningkatkan kesehatan ibu hamil, kesehatan keluarga RTSM/KSM, mengurangi beban hidup, dan meningkatkan pendidikan. Kata kunci: Program Keluarga Harapan, kesehatan, pendidikan, kemiskinan.